Recent trends and patterns in Nigeria's industrial development (2007)
This paper analyses recent trend and spatial patterns of manufacturing in Nigeria. In particular, the paper shows that industrial development in the country involved considerable artisanal crafts firms in the early stages and grew progressively in number over the years to large-scale manufacturing. The pattern of the distribution of manufacturing industries at the city level indicates that there is a marked concentration of manufacturing establishments in the southern part of the country, and especially Lagos, Ibadan and Benin in the southwest. Other locations of relative high concentration of industrial establishments are Kano in the North; and Enugu and Port Harcourt in the southeast. Although, this paper shows that production subcontracting increased and varied amongst subcontracting firms, production subcontracting relationships are concentrated in a few locations. The paper concludes that the spatial pattern could change if industrialists adopt the strategy of industrial linkages, and especially production subcontracting which has become a driving force in contemporary industrial development efforts in the world today. It is expected that the situation could be better enhanced given the ongoing privatisation of industrial concerns in Nigeria.